The Urgency of Restorative Justice Regulation on Hate Speech - Bawono, Bambang Tri; Glaser, Henning (BESTUUR, 2023)
Regulations on the imposition of criminal sanctions in cases of hate speech on social media are, at some point, considered to degrade human rights to express opinions in the context of a democratic country. This research aims to provide an overview of resolving hate speech cases on social media using a restorative justice approach and how regulations should be created and developed. This research uses normative legal research methods using statutory and conceptual approaches. The concept proposed refers to the theory of restorative justice and the theory of establishing appropriate regulations. This research indicates that until now, there has been no strong and adequate legal basis for implementing non-penal resolution of hate speech cases through a restorative justice approach. In the Criminal Code, which revokes the article regarding hate speech in the Information and Electronic Transactions Law both before and after the Constitutional Court Decision, there is no reference to using a restorative justice approach in resolving existing cases. It is urgent to regulate restorative justice arrangements to guarantee legal certainty for the parties by considering recovery for damage and losses victims suffer based on a mutually agreed agreement. Restorative justice can mediate accusations of degradation of freedom of opinion and can maintain democratic values. Based on the regulatory formation process theory, some factors must be considered in designing and making restorative justice arrangements in hate speech cases.